Penentuan Stok Persediaan Bahan Baku Guna Mengurangi Biaya Penyimpanan Pada Bayu Akrilik Menggunakan Metode Continuous Review System - Zein, Muhammad Rifqi; Herlina, Herlina (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
Bayu Akrilik is an acrylic printing and decoration industry in Surabaya with a Make to Order (MTO) production system. However, the company faces challenges in managing raw material inventory, especially acrylic sheets with a thickness of 2 mm and 3 mm. The main problem is the accumulation of stock and shortage of raw materials due to fluctuations in demand and suboptimal purchases. Inefficient inventory management causes increased storage costs, including electricity costs, salaries, rent, and other additional costs, which have an impact on increasing total operating costs. This study uses the Naïve method for demand forecasting, with the results showing the lowest Mean Absolute Percent Error (MAPE). In addition, the Continuous Review System method is applied to determine the optimal safety stock, reorder point, and economic order quantity (EOQ). For 2 mm acrylic, the safety stock is 6 sheets, with an ROP of 26 sheets, while for 3 mm acrylic, the safety stock is 8 sheets, with an ROP of 33 sheets. Keywords: Acrylic, CRS, Inventory Management, MTO.